권오상의 정물 조각에 나타난 구축과 해체의 공존 - 이문정; Lee Moon Jung (기초조형학연구, 2022)
본 논문은 구축과 해체의 공존에 초점을 맞춰 권오상의 정물 조각이 보여주는 형식과 주제를 연구하는 것을 목적으로 한다. 연구를 위한 이론적 근거로는 존재와 소유, 인간의 욕망, 자본주의와 소비사회에 관한 에리히 프롬(Erich Fromm)의 이론과 기 드보르(Guy Debord)의 스펙터클(spectacle) 개념을 선택했다. 스펙터클과 관련해 소비문화에 관한 장 보드리야르(Jean Baudrillard)의 논의도 일부 적용되었다. 연구의 방법은, 형식적인 면에서 사진과 조각, 이미지와 물질, 가상과 실재의 경계를 해체하면서도 조각의 정체성을 공고히 하는 이중성을 분석했다. 주제적인 면에서는 인간의 소유 욕망과 바니테(vanité)의 양가성을 고찰했다. 또한 고도로 추상화된 상품화가 일상생활에 침투하고 이미지 과잉이 되어버린 사회를 지배하는 스펙터클의 재현과 해체도 살펴보았다. 결과적으로 일상의 사물을 촬영한 사진, 잡지나 인터넷에서 선택한 이미지를 바탕으로 제작된 권오상의 정물 조각은 소비와 소유가 그 자체로 욕망의 대상이 되고, 상품이 단순한 물적 대상이 아닌 자기 표현의 상징물로 존재하게 된 오늘날의 소비문화를 투영한다. 또한 소비문화의 견고한 위상을 확인시키는 동시에 그것의 허상을 드러내고, 인간의 욕망과 소유에 관한 근원적인 고찰뿐 아니라 스펙터클 시대에 대한 비판적 사유의 기회를 제공한다. 이를 위해 권오상은 스펙터클의 압도적인 권력을 직관적으로 보여주지만, 실제 사물을 첨가하거나 이미지를 지워 물질성을 강조하는 등의 방법으로 스펙터클과의 단절을 시도한다. 이와 같은 연구를 통해 시대에 반응하며 다양성의 공존과 차이를 창출하는 동시대 조각의 특성을 확인하고, 소비문화에 대한 예술적 성찰이 가져오는 의미 생성을 숙고할 수 있었다. The objective of this thesis is to research the form and subject shown in Osang Gwon’s still-life sculptures by focusing on the coexistence of constructing and disassembling. As the theoretical basis for this study, Erich Fromm’s theory on the existence and possession, human desire, capitalism, and consumer society, and Guy Debord’s concept of spectacle were selected. In relation to spectacle, some of Jean Baudrillard’s discussions of consumer society were also applied. In the research method, this study analyzed the duality that would solidify the identity of sculptures and also deconstruct the boundaries between photographs and sculptures, images and objects, and as well as virtuality and reality in the aspect of form. In the aspect of subject, this study considered human desire for possession and ambivalence of vanité. This study also examined the representation and deconstruction of spectacle that was dominating the society, filled with excessive images where the highly-abstracted commercialization penetrated into daily life. As a result, Osang Gwon’s still-life sculptures produced based on the images selected from photographs of daily objects, magazines, or internet, project today’s consumer culture in which both consumption and possession become the objects of desire, and goods exist as a symbol of self-expression rather than simple physical objects. Also, on top of verifying the solid status of consumer culture and revealing its emptiness, they provide an opportunity not only for the fundamental consideration of human desire and possession, but also for a critical interpretation on the spectacle era. For this, Osang Gwon intuitively shows the overwhelming power of spectacle while also attempting the severance from the spectacle through methods like emphasizing the materiality by adding an actual object or erasing an image. Through this study, the researcher was able to verify the characteristics of contemporary sculptures that could create the coexistence of diversity and difference by responding to the time, and also to consider the formation of meanings brought by the artistic introspection on consumer culture.